Development of Arduino-Based Light Energy Transmission Tool to Improve Students’ Conceptual Understanding of Junior High School - Hardianty Lutfiah; Ketut Alit Adi Untara; Unggul Wahyono; Rudi Santoso (Equator Science Journal, 2026)
Light energy transmission is one of the topics in junior high school science (Physics) that potentially causes comprehension difficulties due to its abstract nature when delivered solely through theoretical instruction. A literature review of Arduino-based studies reveals two gaps: first, some studies focused only on measuring light intensity without examining light energy transmission through specific media; second, studies that measured transmission through transparent materials remained limited to ideal laboratory conditions and had not integrated assessments of students' conceptual understanding. This study aimed to develop a light energy transmission measuring teaching aid based on the Arduino ESP32 type, programmed using the Arduino IDE. The ESP32 was selected due to its advantages over conventional Arduino, integrated Wi-Fi and Bluetooth, enabling more accurate sensor readings and real-time data display. The novelty of this study lies in its focus on light energy transmission, utilization of ESP32, an LED flashlight as a contextual light source, testing on nako glass and no medium conditions, and direct assessment of students' conceptual understanding within a single integrated design. The method used in this study is the Research and Development (R&D) method with the ADDIE model design, conducted at SMP Negeri 7 Sigi involving 21 eighth-grade students of class VIII A. Data were analyzed using the N-Gain formula. The results showed an N-Gain score of 0.58 which falls in the moderate category, indicating an improvement in students' conceptual understanding after participating in the learning process by applying teaching aids in the learning.